SCALAR AND VECTOR FIELD LOCALIZATIONS IN A DISTURBED RANDALL-SUNDRUM METRIC WITH A LINEAR PERTURBATION - SIPAYUNG (NIM : 20215014), DAVIT
The Randall-Sundrum metric is modified by adding a perturbation to the extra dimension metric component. In this paper we derive the energy-momentum tensor that represents the perturbation to the original Randall-Sundrum metric and show the similarities and differences between the disturbed Randall-Sundrum model and the original one. In adition, this paper investigates the localization of scalar and vector fields. The localization properties of the disturbed Randall-Sundrum model are better than that of the original Randall-Sundrum model. Both massless dan massive modes of scalar fields are localized for a positive parameter of the warp factor if the perturbation is proportional to the extra dimension coordinate. Massless vector fields in the other hand are localized irrespective of the warp factor parameter.